DECENTRATION AND REFLEXIVITY: A METHODOLOGICAL EXPERIENCE IN THE FIELD OF FRENCH AS A FOREIGN LANGUAGE (Živi jezici: Journal for Foreign Languages and Literatures, 2018)
This article presents a pedagogical experience in the field of French as a Foreign Language in the intercultural context of the Philological Faculty of Belgrade University in 2016. In a classroom environment, interculturality entails a reflexive cultural questioning that leads to decentration, whose final stage sees a positive cultural cross-feeding among the actors. The pitfalls to beware of are acculturation (sympathy versus empathy), authentic documents and lack of contextualization. The two lessons discussed in this article focused on the concept of patrimony – the Serbian slava, the Binche Carnival and the Metohija monasteries. We analyze how our cultural projections, our lack of contextualization and of written documents, as well as the learners’ posture prevented a true intercultural dialogue. Then, as a conclusion, we suggest some strategies and practices that aim at solving the encountered problems, that is at increasing the decentration – organize the group into subgroups, use the flipped classroom model, perform tasks in compliance with the action-oriented approach.
Keywords: didactics in FFL; cultural competence; decentration; reflexivity; empathy; sympathy; intercomprehension